DESIGN OF THE E-ATTENDANCE APPLICATION INFORMATION SYSTEM AT PT. KUSUMA KENCANA JAYA BEKASI - Herlina Ferliyanti; Rio Fanni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Attendance is a record of a person's presence in an organizational, school or work environment. Attendance can be done manually or systematically. Manual recording has many disadvantages such as inaccurate recording, risk of loss and fraud, while systematic recording has many advantages, namely accurate recording, minimal risk of loss and fraud. A system is needed to handle employee attendance such as the E-Attendance system as a tool for HRD in processing employee data so that the goals expected by the company can be achieved in terms of salary calculations based on employee attendance and overtime activities. E-attendance (electronic attendance) is a digital recording system using electronic devices and internet technology. E-attendance can replace manual attendance recording methods such as attendance books or attendance cards. At PT. Kusuma Kencana Jaya Bekasi in recording attendance still uses a manual method that is prone to data loss, so digital attendance recording is made using E-attendance which can facilitate the recapitulation and calculation as well as the retrieval of employee data required by the company.